TECHNOLOGY ASSESSMENT IN ENGINEERING PRACTICE. THE CASE OF BIOLIQ® – FUEL PRODUCTION FROM BIOMASS - Armin GRUNWALD (Management Systems in Production Engineering, 2013)
This paper includes a brief overview of the basic motivations and objectives of TA, followed by a description of the three main operating fields of TA: providing scientific advice for decision‐making in the political system, contributing to public debate, and enriching technology development and engineering practice. These issues will then be considered in more detail by referring to various approaches to the relationship between TA and technology development and by presenting a specific case study of an accompanying TA process over various development stages of the bioliq® process for converting dry biomass into fuel (Biomass to Liquid) and chemicals. The accompanying TA work on the bioliq® process can, as a result of more than ten years of experience, be considered a successful technology assessment as it has opened up a new research field with a highly precautionary aspect on the one hand, and helped to win over technology‐oriented research institutes to reorienting their research work, on the other. The results of the TA studies allowed to assess e.g. the competitiveness of the bioliq® process at a very early stage. The mutual trust built up in the course of the historical development between the parties involved has always been essential for this ongoing accompanying TA process. TA has been proven, in this way, a useful tool to uncover new chances for engineering research and development, and to accompany the research process.